2021
DOI: 10.1093/abm/kaab090
|View full text |Cite
|
Sign up to set email alerts
|

mySmartCheck, a Digital Intervention to Promote Skin Self-examination Among Individuals Diagnosed With or at Risk for Melanoma: A Randomized Clinical Trial

Abstract: Background Regular skin self-examination (SSE) reduces melanoma mortality but is not often conducted. Purpose To promote SSE performance in individuals at increased risk for melanoma. Methods One hundred sixteen individuals at heightened risk for development of melanoma (i.e., personal/family history of melanoma, high-risk mole phenotype) who did not conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…A total of 1566 studies were identified in the database search. After removing duplicates, the screening process, and complete reading of the records that met the eligibility criteria, 17 RCTs were finally included in the review [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The complete process is shown in Figure 1.…”
Section: Study Selection and Methodological Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 1566 studies were identified in the database search. After removing duplicates, the screening process, and complete reading of the records that met the eligibility criteria, 17 RCTs were finally included in the review [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The complete process is shown in Figure 1.…”
Section: Study Selection and Methodological Quality Assessmentmentioning
confidence: 99%
“…The age of the participants ranged from 12.6 to 54.3 years. The digital strategies used in the included RCTs were web-based interventions in 8 studies [35,40,42,43,46,[48][49][50], 6 involved apps [36][37][38]44,45,47], 3 involved SMS [35,36,39], 2 involved video [34,41], and 1 involved a wearable device [47]. Conversely, the comparator groups involved no intervention in 11 studies [35,37,[43][44][45][46][47][48]50] and active controls in 6 studies [34,36,38,39,41,49].…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations